Use of 2-Hydroxy-4-Isopropoxypropiopenone Oxime as a Spectrophotometric Reagent for Iron - Kahar, P.A.; Desai, K.K. (Asian Journal of Chemistry, 2010)
2-Hydroxy-4-isopropoxypropiophenone oxime (HIPPO) hasbeen developed as a new spectrophotometric reagent for iron. Thereagent gives purple coloured Pe(III) complex in the pH range2.0-3.0. The stoichiometry of the complex is found to be 1 : 1 byJob's method and mole ratio method. The molar absorptivity ofcomplex at 490 nm is found to be 1.214 x 103 lit. mol-1 cm-1 andSandell's sensitivity is found to be 0.046 μg/cm2. The stabilityconstant of the complex is found to be 1.41 x 105 and Gibb's freeenergy change for complex formation reaction is calculated to be-7.06 kcal/mol at 27°C. The Beer law is obeyed up to 7.84 ppm ofPe(III) ion. The reagent has been found to give quite satisfactoryresults for the analysis of iron in pharmaceutical preparations anddolomite ore. The reagent has been used as an indicator for thephotometric titration of Pe(III) with EDTA.